Selection of Sustainable Building Material Using Multicriteria Decision-Making Model: A Case of Masonry Work in Lideta Subcity, Addis Ababa - Diriba Tegegne; Mebratu Abera; Esayas Alemayehu (Advances in Civil Engineering)
In today’s world, where the need for construction projects is increasing from time to time, especially in developing countries such as Ethiopia, sustainability issues and principles were not exercised by construction professionals during the material selection process. At the initial stage, the designer considers materials he/she is familiar with. However, their assumption may not work because the structure that is going to be developed may be different from the previous one. Thus, the designer shall consider sustainability issues during the design period. This article will guide construction stakeholders in the selection of sustainable building materials, specifically masonry materials in the Ethiopian construction industry. The research was carried out in the Addis Ababa Lideta subcity, to identify sustainable building materials for masonry work. The selection process is not depending on a single factor rather it depends on multifactors. The identification was carried out through exploring factors affecting the selection of sustainable building materials for masonry work. The weights of identified factors were determined by pairwise comparison among the factors under consideration. The research is of the empirical type which uses mathematical formula, matrix concept, and analytical hierarchy process (AHP) as a model. In this method, pairwise comparisons were made among the criteria and subcriteria so that the weights of the criteria or subcriteria/or alternative on the bases of the indicated criteria were computed. Then, prioritization was made on the bases of the weight of the criteria. Finally, an alternative with a high score shall be selected. The article identifies the major factor affecting the selection of sustainable building materials for masonry work as social benefit, performance capability, sustainability of the material to reduce environmental impact, waste minimization, resource efficiency, and life cycle cost of the material. Under each criterion, there are number of subcriteria contributed to them. On the basis of the above criteria, 4 alternatives (stone, brick, CEB, and cement block) were proposed from which compressed Earth block (CEB) was selected.